El razonamiento repetido en el aprendizaje de la matemática - Quintero Suica, Diana Isabel (Universidad Antonio Nariño, 2023)
Considering the importance of repeated reasoning in the mathematics classroom as a way of consolidating learning, this research seeks to advance in the description, explanation, and enrichment of the processes underlying this reasoning (internalization; organization and reorganization; and retention of knowledge), within the framework of the principle of repeated reasoning postulated by the DNR.